SolarTurtle : searching for the game changer - Urban, Boris; Maphalala, Jabu (London : Wits Business School, 2018)
James van der Walt, founder of SolarTurtle, looked out of his office window at the people sitting in the common area of Stellenbosch University's LaunchLab. Van der Walt's mind was, however, far from the LaunchLab's collegial environment that afternoon in May 2018. SolarTurtle had not been growing fast enough to make the company self-sustaining, and the current finance model for franchisees had proven to be unsustainable. Van der Walt wondered whether the introduction of the BabyTurtle and the MiniTurtle, the company's newest products, would improve the growth rate of the company.
Originally Published In Urban, B., & Maphalala, J. (2018). SolarTurtle: Searching for the Game Changer. WBS-2018-12. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Industrial management -- South Africa -- Stellenbosch -- Decision making -- Case studies; Business enterprises -- South Africa -- Stellenbosch -- Case studies; Franchises (Retail trade) -- South Africa -- Stellenbosch -- Case studies